Incoterms 2000 = Những điều kiện thương mại quốc tế - Nguyễn Trọng Thủy (Tp.HCM : Thống kê, 1999)
The purpose of incoterms is to provide a set of international rules for the interpretation of the most commonly used trade terms in foreign trade.
Keywords: Incoterms; Thương mại quốc tế; Incoterms